THE MEDIATING ROLE OF OUTSOURCING INTERNAL AUDITING IN THE RELATIONSHIP BETWEEN ELECTRONIC AUDITING AND AUDITING STRATEGIES-A FIELD STUDY IN PUBLIC COMPANIES IN IRAQ - Assistant Teacher: Ahmed Abed Ahmed; Dr. Hanen MOALLA (American Journals, 2023)
Through this research, we seek to demonstrate the role of the relationship between electronic auditing and outsourcing internal auditing in supporting auditing strategies for the opinions of a sample of companies operating in Iraq, and to identify the nature of the correlation and influence relationships between the research variables (electronic auditing, outsourcing internal auditing, auditing strategies) in companies under review. Studying.The researcher formulated a set of questions that represented the problem of the research, and for achieving the goal of the research, a hypothetical scheme was adopted through which its hypotheses were defined.The study population consists of some Iraqi companies in Baghdad governorate, while the study sample was limited to internal auditors, accountants, and implementation managers in Iraqi companies, as the number of these companies reached (21) companies, and (3) were excluded as a result of the invalidity of their answers for analysis. So that the number of companies in the study sample is limited to (18) companies only, (210) forms were distributed, as if the recovered and valid ones for analysis were (202) forms only, i.e. with a recovery rate of only 96%, and then the researcher analyzed them using the appropriate statistical program.The study came out with a set of results, the most important of which is the impact of electronic auditing and outsourcing of internal auditing in supporting auditing strategies in the companies under study. In order to prepare the report and guide the development of the audit plan, the disclosure of the comprehensive audit strategy must contain sufficient details to guide them when developing the internal audit plan or outsourcing, so that the audit strategy is comprehensive.
Keywords: Electronic audit, outsourcing internal audit, audit strategies